A proteomic study on molecular mechanism of poor grain-filling of rice (Oryza sativa L.) inferior spikelets. - Zhixing Zhang; Hong Zhao; Jun Tang; Zhong Li; Zhou Li; Dongmei Chen; Wenxiong Lin (PLoS ONE)
Cultivars of rice (Oryza sativa L.), especially of the type with large spikelets, often fail to reach the yield potential as expected due to the poor grain-filling on the later flowering inferior spikelets (in contrast to the earlier-flowering superior spikelets). The present study showed that the size and grain weight of superior spikelets (SS) was greater than those of inferior spikelets (IS), and the carbohydrate supply should not be the major problem for the poor grain-filling because there was adequate amount of sucrose in IS at the initial grain-filling stage. High resolution two-dimensional gel electrophoresis (2-DE) in combination with Coomassie-brilliant blue (CBB) and Pro-Q Diamond phosphoprotein fluorescence stain revealed that 123 proteins in abundance and 43 phosphoproteins generated from phosphorylation were significantly different between SS and IS. These proteins and phosphoproteins were involved in different cellular and metabolic processes with a prominently functional skew toward metabolism and protein synthesis/destination. Expression analyses of the proteins and phosphoproteins associated with different functional categories/subcategories indicated that the starch synthesis, central carbon metabolism, N metabolism and cell growth/division were closely related to the poor grain-filling of IS. Functional and expression pattern studies also suggested that 14-3-3 proteins played important roles in IS poor grain-filling by regulating the activity of starch synthesis enzymes. The proteome and phosphoproteome obtained from this study provided a better understanding of the molecular mechanism of the IS poor grain-filling. They were also expected to be highly useful for improving the grain filling of rice.